The Effect of Using Augmented Reality (AR) Assembler to Improve Scientific Explanation and Student Interest in Science Learning - A. Masrurah Aswidyaningrat; Yuninda Adumiranti; Sabar Nurohman; Winarto Winarto (Universitas Negeri Semarang, 2025)
This study aims to analyze the effect of using Augmented Reality (AR) assisted by Assembler in improving the ability of scientific explanation and student interest in learning science. The method used was quasi-experimental with a one-group pretest-posttest design on 20 seventh grade students of SMP Muhammadiyah 3 Depok. Data were collected through scientific explanation ability test and learning interest questionnaire, then analyzed using Paired Sample t-test and Cohen’s d to measure the intervention effect. The results showed a significant increase in scientific explanation ability and interest in learning. The highest scientific explanation indicator is in claim, while interest in learning is dominated by aspects of attention and feelings of pleasure. The findings prove that Augmented Reality (AR) is effective as an innovative learning media to improve the understanding of science concepts and students’ learning motivation. The implications of the research encourage the integration of Augmented Reality (AR) technology in the science curriculum to create interactive and meaningful learning experiences.